2017
DOI: 10.21726/rsbo.v13i2.275
|View full text |Cite
|
Sign up to set email alerts
|

Oral diseases diagnosis rate during an oral cancer prevention campaign in Fernandópolis, Brazil, 2014

Abstract: Introduction: Oral cancer is a worrying disease which claims for actions aiming its early diagnosis and prevention. Objective: To describe lesions diagnosed during oral cancer prevention campaign performed in the city of Fernandópolis, Brazil, in 2014. Material and methods: Patients who attended for the basic health units of the city of Fernandópolis on the day of the campaign were examined by a previously trained dentist who searched for oral lesions suggestive for oral squamous cell carcinoma or potentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…On the other hand, we observed that 102 patients were referred for reassessment by a specialist due to suspicious lesions and 94 attended the DSCs for final diagnosis. Although 8 patients were lost, in two previous publications by our group describing results from previous campaigns in 2014 10 and in 2015 11 , the number of patients who did not attend for final diagnosis were, respectively, 40 and 24. A decrease in the number of patients who do not show for the final diagnosis is clear.…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, we observed that 102 patients were referred for reassessment by a specialist due to suspicious lesions and 94 attended the DSCs for final diagnosis. Although 8 patients were lost, in two previous publications by our group describing results from previous campaigns in 2014 10 and in 2015 11 , the number of patients who did not attend for final diagnosis were, respectively, 40 and 24. A decrease in the number of patients who do not show for the final diagnosis is clear.…”
Section: Discussionmentioning
confidence: 85%